Perception toward Biosimilars and Nonmedical Switching: A Cross-sectional Survey among Arab Rheumatologists - Mohammed A. Omair; Humaid Al Wahshi; Jamal Al Saleh; Farida Al Balushi; Mostafa Zayed; Maha A. Omair; Eduardo Mysler (Dr. Sulaiman Al Habib Medical Journal)
Objective: The aim of this study is to assess the level of knowledge and acceptance for biosimilars and nonmedical switching in Arab rheumatologists. Methods: A cross-sectional survey was conducted during the Arab League Against Rheumatism conference using a structured questionnaire consisting of 17 questions. Results: The participants were mainly females (50.7%), practicing in the Gulf region (65.7%) with a median [Interquartile Range (IQR)] age and years of practice as consultants of 44 (13) years and 10 (14) years, respectively. The median (IQR) self- perceived knowledge of biosimilars was 5.3 (4) out of 10. Most physicians agreed that the evidence published to grant biosimilars an approval for the studied indication was enough (40.6%), yet most of them believed it was not enough for extrapolation of indications (40.6%). The mean (standard deviation) likelihood to prescribe biosimilars in the future was 5.39 (2.6). The majority of rheumatologists (59.8%) believe that nonmedical switching could pose harm to patients. Most physicians agreed that nonmedical switching will lead to a significant saving in cost (58.5%) with the majority expecting a cost reduction between 30% and 50% to justify nonmedical switching. Conclusion: This is the first study to evaluate acceptance of biosimilars and nonmedical switching on a diverse population of rheumatologists in the Middle East. Future educational activities task forces should target these topics.